Epididymal more than testicular abnormalities are associated with the occurrence of antisperm antibodies as evaluated by the MAR test. Issue 8 (4th July 2018) - Lotti, F; Baldi, E; Corona, G; Lombardo, F; Maseroli, E; Degl'Innocenti, S; Bartoli, L; Maggi, M
Abstract: STUDY QUESTION: Is there any association between mixed antiglobulin reaction (MAR) test positivity and clinical features or genital tract ultrasound (US) parameter values in males of infertile and fertile couples? STUDY ANSWER: In males of infertile and fertile couples MAR test positivity was associated with clinical and US features suggestive of chronic epididymal inflammation. WHAT IS KNOWN ALREADY: MAR test positivity has been more often reported in males of infertile couples than in fertile men. A positive MAR test has been detected in men with a history of testicular or post-testicular damage. No previous study has reported US alterations related to MAR test positivity. This is the first study that has systematically evaluated associations between a positive MAR test and clinical, seminal and US characteristics of the entire male genital tract. STUDY DESIGN, SIZE, DURATION: This cross-sectional analysis included 109 fertile men and 699 consecutive subjects seeking medical care for couple infertility from September 2012 to September 2017. PARTICIPANTS/MATERIALS, SETTING, METHODS: All subjects underwent, in our outpatient clinic, a complete physical, endocrine, scrotal and transrectal US evaluation and semen analysis (including sIL-8) on the same day. Of the 699 males of infertile couples, 181 (age 38.6 ± 6.6 years) had an assessable MAR test, whereas the test was assessable in all 109 fertile men (age 36.6 ± 5.2 years). The associations among MAR test positivity and the other studied parameters were investigated on a caseload of 290 men (patients + fertile men) and in the two cohorts of males of infertile and fertile couples. MAIN RESULTS AND THE ROLE OF CHANCE: Of the 181 men of infertile couples studied, 20 (11%) had a positive MAR test, including 12 (6.6%) who had a MAR test ≥ 50%, which is considered as a pathological threshold according to the WHO. Of the 109 fertile men, four (3.7%) had a positive MAR test, of which one (0.9%) had a MAR test ≥ 50%. MAR test positivity was therefore found more often in men of infertile couples ( P < 0.05). In the entire caseload ( n = 290) of males of both infertile and fertile couples, no correlations between MAR test positivity and seminal characteristics were observed. A positive MAR test was associated with epididymal US abnormalities, particularly with the mean size of the epididymal body and tail (both P < 0.0001), and in infertile men, a positive MAR test was also associated with an abnormal epididymal echotexture. In addition, subjects with a positive MAR test more frequently showed a history of epididymitis and high sIL-8 levels. Considering endocrine parameters, only a positive correlation between MAR test positivity and LH levels was observed, even after adjusting for age and life-style factors (adj. r = 0.232, P < 0.0001), while no associations with testosterone and FSH levels were found. LIMITATIONS, REASONS FOR CAUTION: Antisperm antibodies (ASA) were detected in this study by using the SpermMAR test IgG, but other tests are available. In addition, for technical reasons, the MAR test is not assessable in subjects with severe oligo-astheno-zoospermia and, therefore, this test may lead to an intrinsic selection bias. Finally, owing to the cross-sectional nature of the study, neither a causality hypothesis nor mechanistic models can be inferred. WIDER IMPLICATIONS OF THE FINDINGS: First, our results indicate that MAR test positivity is associated with clinical and US signs suggestive of chronic epididymal inflammation and not testicular damage. Hence, when investigating a subject with a positive MAR test, the epididymis and not just the testis should be evaluated. Furthermore, MAR test positivity was more often detected in males of infertile couples than in fertile men, but it was not associated with conventional semen parameter values. Our data support a role of ASA in couple infertility, regardless of the conventional sperm analysis. How ASA affects couple fertility needs to be addressed by further studies. STUDY FUNDING/COMPETING INTEREST(S): Grants were received from the Ministry of University and Scientific Research (SIR project to F.L., protocol number: RBSI14LFMQ). There are no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.